5(y-1)=6(y-5)

Simple and best practice solution for 5(y-1)=6(y-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y-1)=6(y-5) equation:


Simplifying
5(y + -1) = 6(y + -5)

Reorder the terms:
5(-1 + y) = 6(y + -5)
(-1 * 5 + y * 5) = 6(y + -5)
(-5 + 5y) = 6(y + -5)

Reorder the terms:
-5 + 5y = 6(-5 + y)
-5 + 5y = (-5 * 6 + y * 6)
-5 + 5y = (-30 + 6y)

Solving
-5 + 5y = -30 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-5 + 5y + -6y = -30 + 6y + -6y

Combine like terms: 5y + -6y = -1y
-5 + -1y = -30 + 6y + -6y

Combine like terms: 6y + -6y = 0
-5 + -1y = -30 + 0
-5 + -1y = -30

Add '5' to each side of the equation.
-5 + 5 + -1y = -30 + 5

Combine like terms: -5 + 5 = 0
0 + -1y = -30 + 5
-1y = -30 + 5

Combine like terms: -30 + 5 = -25
-1y = -25

Divide each side by '-1'.
y = 25

Simplifying
y = 25

See similar equations:

| 1/3x-6=4+2x | | 9+8x=93 | | 4=7v-8/8+v-6/4 | | 4b-6-12b-4= | | 2x+3y=2772 | | x-25=5+11x | | K=-5/2 | | 3y-(-4y+3)=-17 | | (x-2)/6=(x+3)/9 | | 35-8x=22 | | 7(6+2)= | | -(5a+4)+1=2-(5a-1) | | -22.4+6x=75.5 | | t/-17.7=-12.7 | | -(2a-2)+3=3-(2a+5) | | 6(3-2)x=54 | | 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 |

Equations solver categories